The Effect Of Work Engagement, Work Environment, And Job Satisfaction On Turnover Intention On Employees Of Cv Joglo Furniture In Yogyakarta - Hanifa Dewi Febriana; Prayekti Prayekti; Epsilandri Septyarini (Jurnal Ilmu Manajemen Profitability, 2022)
The purpose of this study was to determine the effect of work involvement, work environment and job satisfaction on turnover intention of employees at CV. Joglo Furniture Yogyakarta. This type of research is research with a quantitative approach. This study uses the saturated sample method, where the entire population is the research sample. The number of samples is 48 respondents and the results of the analysis use SPSS Version 25. Based on the results of data analysis on the t test, it can be concluded that work involvement has no negative and significant effect on turnover intention, as evidenced by the regression coefficient value of 3,004, while the significant value is 0.025 0.050. The work environment is stated to have a negative and significant influence on turnover intention, as evidenced by the coefficient value of -3.098, while the significant value is 0.013 0.050, which means that the worse the work environment for employees, the higher the turnover intention. Job satisfaction has a negative and insignificant effect on turnover intention, as evidenced by the regression coefficient value of -0.167, while the significant value is 0.7210.050. In the F test results, work involvement, work environment and job satisfaction simultaneously affect turnover intention, which is indicated by a significant value of 0.031 0.05.